Detection of PIK3CA Gene Mutations with HRM Analysis and Association with IGFBP-5 Expression Levels in Breast Cancer - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Breast cancer is the second most common cancer and second leading cause of cancer deaths in women. Phosphatidylinositol-3-kinase (PI3K)/AKT pathway mutations are associated with cancer and phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) gene mutations have been observed in 25-45% of breast cancer samples. Insulin growth factor binding protein-5 (IGFBP-5) can show different effects on apoptosis, cell motility and survival in breast cancer. We here aimed to determine the association between PIK3CA gene mutations and IGFBP-5 expressions for the first time in breast cancer patients. Frozen tumor samples from 101 Turkish breast cancer patients were analyzed with high resolution melting (HRM) for PIK3CA mutations (exon 9 and exon 20) and 37 HRM positive tumor samples were analyzed by DNA sequencing, mutations being found in 31. PIK3CA exon 9 mutations (Q546R, E542Q, E545K, E542K and E545D) were found in 10 tumor samples, exon 20 mutations (H1047L, H1047R, T1025T and G1049R) in 21, where only 1 tumor sample had two exon 20 mutations (T1025T and H1047R). Moreover, we detected one sample with both exon 9 (E542Q) and exon 20 (H1047R) mutations. 35% of the tumor samples with high IGFBP-5 mRNA expression and 29.4% of the tumor samples with low IGFBP-5 mRNA expression had PIK3CA mutations (p=0.9924). This is the first study of PIK3CA mutation screening results in Turkish breast cancer population using HRM analysis. This approach appears to be a very effective and reliable screening method for the PIK3CA exon 9 and 20 mutation detection. Further analysis with a greater number of samples is needed to clarify association between PIK3CA gene mutations and IGFBP-5 mRNA expression, and also clinical outcome in breast cancer patients.
Keywords: PIK3CA; PI3K; IGFBP5; HRM assay; Turkish breast cancer; mutation; FACTOR BINDING-PROTEINS; GROWTH-FACTOR; PATHWAY; KINASE; SUSCEPTIBILITY; PROLIFERATION; METASTASIS; OVARIAN; ROLES; CELLS